Effect of comprehensive cardiac telerehabilitation on one-year cardiovascular rehospitalization rate, medical costs and quality of life: A cost-effectiveness analysis. (May 2016) - Frederix, Ines; Hansen, Dominique; Coninx, Karin; Vandervoort, Pieter; Vandijck, Dominique; Hens, Niel; Van Craenenbroeck, Emeline; Van Driessche, Niels; Dendale, Paul
Background: Notwithstanding the cardiovascular disease epidemic, current budgetary constraints do not allow for budget expansion of conventional cardiac rehabilitation programmes. Consequently, there is an increasing need for cost-effectiveness studies of alternative strategies such as telerehabilitation. The present study evaluated the cost-effectiveness of a comprehensive cardiac telerehabilitation programme. Design and methods: This multi-centre randomized controlled trial comprised 140 cardiac rehabilitation patients, randomized (1:1) to a 24-week telerehabilitation programme in addition to conventional cardiac rehabilitation (intervention group) or to conventional cardiac rehabilitation alone (control group). The incremental cost-effectiveness ratio was calculated based on intervention and health care costs (incremental cost), and the differential incremental quality adjusted life years (QALYs) gained. Results: The total average cost per patient was significantly lower in the intervention group (€2156 ± €126) than in the control group (€2720 ± €276) ( p = 0.01) with an overall incremental cost of €–564.40. Dividing this incremental cost by the baseline adjusted differential incremental QALYs (0.026 QALYs) yielded an incremental cost-effectiveness ratio of €–21, 707/QALY. The number of days lost due to cardiovascular rehospitalizations in the intervention group (0.33 ± 0.15) was significantly lower than in the control group (0.79 ± 0.20) ( p = 0.037). Conclusions: This paper shows the addition of cardiac telerehabilitation to conventional centre-based cardiac rehabilitation to be more effective and efficient than centre-based cardiac rehabilitation alone. These results are useful for policy makers charged with deciding how limited health care resources should best be allocated in the era of exploding need.